COMPARATIVE CALORIFIC ANALYZES OF COCONUT SHELL AND DURIAN FRUIT PEEL BY USING DIFFERENTIAL SCANNING CALORIMETRY - Safri Gunawan; Banu Nursanni; Sapitri Januariyansah; Suprapto Suprapto (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
The production of coconut and durian means that it will produce a lot of waste from its shell. Indonesia is a country that produces a lot of them. The coconut shell (CS) and durian fruit peel (DFP) can be converted to briquette as new fuel from biomass. The objective of this research is to obtain the calorific briquette properties of CS and DFP using Differential Scanning Calorimetry (DSC). The material composition consist of 10 % and 15 % of starch for each CS and DFP. Thermal treatment was carried out in the temperature range of 28 °C to 600 °C at 5.4 °C/min. The addition of starch causes the heating temperature since it has thermoplastic properties. Additionally, it is difficult to burn and carries a lot of water so that the heat generated is used to evaporate the water first of all in the briquettes. The recommended material is CS with 10 % mass of starch. The optimum temperature reached was 578.97 °C with an enthalpy value of 0.42 J/g.